Quranic-based Moderate Islam in Pesantren against Radicalism - Al Qudus Nofiandri Eko Sucipto Dwijo; Muhammad Fahmi; Saefullah Azhari; Senata Adi Prasetia; Salman Al Farisi (UIN Sunan Ampel Surabaya, 2022)
This article investigates counter-radicalism practices through the development of wasathiyah Islamic teachings at the Raudlotul Huffadz Pondok Pesantren (PPRH) in Tabanan, Bali. The competition between radical and moderate Muslims (wasathiyah) is intensifying. In this instance, the existence of radical extremist groups is the reason moderate Islam (wasathiyah) exists. This article explains that the practice of counterradicalism through the construction of Al-Quran-based Wasathiyah Islamic teachings in the PPRH takes the form of constructing and developing moderate, tolerant, anti-radicalization, and rahmatan lil alamin Islamic teachings to combat radicalism movements that are frequently attributed to the Quran. At PPRH, the tahfidz al-Quran assembly is created, in which Islamic values of wasathiyah and anti-religious radicalism are taught. This program is a countermeasure against non-Sanad tahfidz al-Quran houses, which tend to teach religious values with radical overtones. In fact, the Al-Qur’an, as the primary source of Islamic teachings, must be investigated in terms of wasathi narratives and Islamic movements as part of peaceful and rahmatan lil'alamin Islamic teachings.